2018
DOI: 10.1108/tlo-02-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Crossing power and knowledge boundaries in learning and knowledge sharing

Abstract: As soon as we've published an article, the version of the article that has been accepted for publication, the Author Accepted Manuscript (AAM) can be used for a variety of non-commercial scholarly purposes, subject to full attribution. An author may deposit and use their AAM (aka post-print)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…Particularly, in this specific case, as well as found in other cases reported in the literature [41,42,55,56] we also noticed that language-related boundaries as well as the different views on the problem were very pronounced between involved social actors, since it is (1) a typically multifaceted territorial problem involving many different actors and (2) takes place in a vulnerable context in which there are accentuated cultural differences.…”
Section: The Main Boundary Object: the Degradation Of The Taquara Strsupporting
confidence: 81%
“…Particularly, in this specific case, as well as found in other cases reported in the literature [41,42,55,56] we also noticed that language-related boundaries as well as the different views on the problem were very pronounced between involved social actors, since it is (1) a typically multifaceted territorial problem involving many different actors and (2) takes place in a vulnerable context in which there are accentuated cultural differences.…”
Section: The Main Boundary Object: the Degradation Of The Taquara Strsupporting
confidence: 81%
“…The case study confirmed that creative abrasion is unavoidable when people antagonize each other's interests. A recent case study (Filstad et al, ) of bureaucratic and hierarchical public organizations confirmed Carlile's () theory that differences between actors result in negotiations over existing practices and the creation of new knowledge. Those findings can be considered similar to ours because both reveal that new practices that are consistent with common interests emerge as a result of creative friction.…”
Section: Discussionmentioning
confidence: 63%
“…In fact, more than 90% of organizational learning studies published in major journals from 2000 to 2010 were quantitative (Alok, ). One recent study (Filstad, Simeonova, & Visser, ) suggested that some organizational learning tools (e.g., social media) serve as mere tools of information transfer and do not lead to the development of common meanings and practices among members.…”
Section: Introductionmentioning
confidence: 99%
“…The succession of these 4 capsules mirrors the 4 principle concepts promoted by the model of organisational management proposed in the ShareLab (Fig. 2), namely (1) shared awareness (Carroll et al 2003), ( 2) sharing (Filstad et al 2018), (3) common ground (Murer et al 2014) and (4) cognitive and operational synchronisation (Darses and Falzon 1996).…”
Section: Bim'sharelab Principlesmentioning
confidence: 72%